Modeling of dynamic behavior of printed circuit board (PCB) subjected to mechanical shock loading - Lau, Chin Wei (2006)
The reliability assessments of PCB and PCB related products had been adopted by industries for years. Among the reliability test, mechanical shock damage is one of the most predominant modes of failure when PCB experience deformation that creates excessive strain. For dynamic analysis, it is very expensive, time consuming and difficult to conduct drop/shock test to detect the damage mechanisms and identify their behaviors. However, this assessment can be performed through a computer simulation by Finite Element Method (FEM). FEM is one of such techniques to achieve solution within reasonable computational time and cost. This study presents dynamic analysis of PCB and PCB devices by FEM. As a fundamental study, the natural dynamic properties of a bare PCB and workstation chassis are obtained by FEM and verified with impact hammer test. Good agreement of natural frequencies and mode shapes had been shown between FEM and tested results. From the verified dynamic properties, the shock analysis was carried out further for PCB with components. Two different ways had been carried out. First, to model the drop impact behavior, the free-fall of PCB with attached chips was modeled for seven drop orientation. The bouncing motion was captured and the dynamic responses on all chips had been analyzed and had good agreement compared to reported research. The second impact analysis is done by simulate the PCB with chips that fixed on a drop block. To implement the input-G method, a short impulse was impose to the PCB fixture surface. The natural dynamic behavior was obtained for fixed boundary condition followed by detail deflection motion of PCB due to impact. The simulated result shows that the center of PCB experiences greatest impact, which is well verified with recent related research.